Da’wah Management Strategy on Social Media to Attract the Millennial Generation - Mutmainna, Nurunnisa; Tu, Nguyen Minh; Lan, Tran Thi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The millennial generation’s engagement with social media has significantly influenced the dissemination of religious content, including Islamic da’wah. Traditional da’wah methods relying on in-person gatherings and textual resources face challenges in reaching a digitally connected audience. Social media platforms provide an opportunity for da’wah practitioners to engage millennials through interactive, visually appealing, and accessible content. Understanding effective da’wah management strategies on social media is crucial for optimizing digital Islamic outreach. This study aims to explore effective strategies for managing da’wah content on social media to attract and engage the millennial generation. A qualitative research design is employed, incorporating content analysis of social media da’wah campaigns, interviews with digital da’wah practitioners, and audience engagement metrics. Findings reveal that short-form video content, storytelling techniques, and interactive discussions significantly enhance engagement among millennials. Social media algorithms prioritize content that encourages interaction, requiring da’wah initiatives to integrate consistent posting schedules, audience feedback mechanisms, and visually engaging formats. The study concludes that effective da’wah management on social media necessitates a balance between religious authenticity and digital communication trends.